Let's solve the questions one at a time.
1. Simplify \(5^{10} \times 5^{5}\)
Using the Product Rule of Exponents: \[ 5^{10} \times 5^{5} = 5^{10 + 5} = 5^{15} \]
Answer: \(5^{15}\)
2. Find the numerical equivalent of \(9^{9} \times 9^{-6}\)
Using the Property of Exponents: \[ 9^{9} \times 9^{-6} = 9^{9 - 6} = 9^{3} \]
Calculating \(9^{3}\): \[ 9^{3} = 729 \]
Answer: \(729\)
3. What is the missing exponent in the equation \(h^{450}/h^{?} = h^{215}\)?
Using the Quotient Rule of Exponents: \[ h^{450 - ?} = h^{215} \implies 450 - ? = 215 \implies ? = 450 - 215 = 235 \]
Answer: \(235\)
4. Simplify \(12^{87}/12^{25}\)
Using the Quotient Rule of Exponents: \[ 12^{87} / 12^{25} = 12^{87 - 25} = 12^{62} \]
Answer: \(12^{62}\)
5. What is the missing number in the expression \(7^{?} / 7^{5} = 7^{12}\)?
Using the Quotient Rule of Exponents: \[ 7^{? - 5} = 7^{12} \implies ? - 5 = 12 \implies ? = 12 + 5 = 17 \]
Answer: \(17\)
6. Evaluate \(6.9^{-2}\)
The expression \(6.9^{-2} = \frac{1}{6.9^{2}}\):
Calculating \(6.9^{2} = 47.61\):
Thus, \[ 6.9^{-2} = \frac{1}{47.61} \]
Keeping the answer in decimal is less clear, let's re-evaluate:
If simply to get value:
- Using direct calculation \(6.9 = \frac{1}{(6.9)^2}\approx 0.02041649\)
When using in approximation close enough to: Converting more:
Answer: \(0.0204\) or expressed simply as the round-off \(0.0208\) or \(5.9\).
7. Apply the Zero Power Rule.
Using the Zero Power Rule: \[ (-33)^{0} = 1 \text{ and } 27^{0} = 1 \] Thus, the expression simplifies to: \[ 9 + \frac{3}{2}(8 - 1) = 9 + \frac{3}{2}(7) \]
Answer: \(9 \times 1 + \frac{3}{2} \times 7\)
8. Solve \(15x8^{0}/5 + 4(7^{0}-6)\)
\[ 8^{0} = 1, \quad 7^{0} = 1 \] So, we have: \[ \frac{15 \times 1}{5} + 4(1 - 6) = 3 + 4(-5) = 3 - 20 = -17 \]
Answer: \(-17\)
9. Simplify \((10^{3})^{6}\)
Using the Power Rule of Exponents: \[ (10^{3})^{6} = 10^{3 \times 6} = 10^{18} \]
Answer: \(10^{18}\)
10. Expand \(7^{15}\)
The expanded equivalent expression for \(7^{15}\): \[ (7 \cdot 7 \cdot 7 \cdots 7) \text{ (15 times)} \]
Answer: \(7^{15} = (7 \cdots 7) \text{ (15 terms)}\)
11. Simplify \((19^{4})^{9}\)
Using the Power Rule: \[ (19^{4})^{9} = 19^{4 \cdot 9} = 19^{36} \]
Answer: \(19^{36}\)
12. Simplify \(7^{-3}\)
Using the positive exponent property: \[ 7^{-3} = \frac{1}{7^{3}} \] \[ 7^{3} = 343 \]
Answer: \(\frac{1}{343}\)
13. Convert \(3^{-17}/8^{-14}\) to positive exponents.
\[ 3^{-17}/8^{-14} = \frac{3^{-17}}{8^{-14}} = \frac{8^{14}}{3^{17}} \text{ (by taking negative out)} \]
Answer: \(\frac{8^{14}}{3^{17}}\)
14. Solve \((7^{-3})^{7} \cdot 7^{20}/6^{-2}\)
Step 1: Convert to positive exponents: \[ (7^{-3})^{7} = 7^{-21}, \quad 6^{-2} = \frac{1}{6^{2}} \]
Thus, simplifying: \[ \frac{7^{-21} \cdot 7^{20}}{6^{-2}} = \frac{7^{-21+20}}{1/6^{2}} = \frac{7^{-1}}{1/6^{2}} = \frac{6^{2}}{7^{1}} = \frac{36}{7} \]
Final Implied Answer: \[ \frac{36}{7} \]